Air quality and confirmed cases of covid-19 in the metropolitan region of Porto Alegre/RS: Ecological study (Revista Contexto & Saúde, 2025)
This study aimed to investigate the relationship between air quality in the municipalities of Canoas and Esteio/RS and reported cases of COVID-19 from March 1, 2020 to February 28, 2021. The analysis was realized by searching and relating air quality data for NO 2 , SO 2 , MP 10 and MP 2.5 obtained from the database of the Fundação Estadual de Proteção Ambiental Henrique Luis Roessler- RS (FEPAM) and data from patients reported with COVID-19 provided by the Federal Government. A prevalence of patients infected by COVID-19 in females (54%) between 30 and 39 years old (23%) was observed in both municipalities. The most listed symptoms were dyspnea (83%) and sore throat (74%) and the most common comorbidities presented by infected patients were asthma (5.37%) in Canoas and Chronic Heart Disease (6.17%) in Esteio. The pollutant values analyzed showed fluctuations and even exceeded the established limits, and a positive statistic (
Keywords: SARS-CoV-2; Pollution; Air quality